Unemployment among Active Population and Poverty Level in Nigeria - Adekunle, Ahmed Oluwatobi (Indonesian Academy of Social and Religious Research (IASRR), 2025)
The socioeconomic problems of poverty and unemployment among the active population are interwoven and continue to impede Nigeria's capacity for progress. Despite being the one of the biggest economies in Africa, the nation struggles to create jobs, especially for its growing youth population. The National Bureau of Statistics (NBS) reports that in the first quarter of 2021, Nigeria's unemployment rate increased to more than 33%, with youth unemployment making up about 53% of the country's total unemployed population. Increased poverty, social discontent, and economic stagnation are all consequences of this escalating crisis for both people and society. Following this, this study aims to evaluate unemployment among active population and poverty level in Nigeria. The participants in this study were residents of Ogun State's Ilaro metropolis. The sample size was calculated using the population figure, from which a total of 128 responders were chosen. The research selected for this study was survey research design and Taro Yamane's formula was utilized. The results based on respondents' responses show that Nigerian government should implement comprehensive educational reforms that focus on equipping students with practical skills relevant to the job market. Additionally, 13 of the respondents strongly disagreed that initiatives to encourage entrepreneurship among the youth should be prioritized. The study recommends development of initiatives to lower youth unemployment and poverty, the government should work with non-governmental organizations (NGOs) and foreign organizations. These collaborations can guarantee the successful execution of projects and improve resource mobilization.